Preclinical testing of new domestic supramolecular complex of triclabendazole «Triclafascid» embryotrophic activity - M. V. Milenina; M. B. Musaev (Российский паразитологический журнал, 2019)
The purpose of the study: embryotoxic and teratogenic effects of a new domestic supramolecular complex of triclabendazole “Triclafascid”. Materials and methods. Embryotoxic and teratogenic effects of new domestic formulations studied Triclafascid accordance with the “Manual on experimental (preclinical) study of new pharmacological substances”. The study embryotrophic actions supramolecular complex preparation on the basis of the substance of triclabendazole was performed on 40 white mongrel female rats weighing 220-260g and 10 males, in accordance with the guidelines on the assessment of the impact of drugs on generative function of animals. To rats-females were placed overnight male ratio of 1:4. Detection of sperm in the vaginal smear, the females, on the morning after the infusion of the male is pointed at fertilization -the first day of pregnancy. Since the sensitivity of the embryo to chemical and depends on the various stages of fetal development, the animals were divided into 4 groups of 10 animals each. Triclafascid was administered orally to pregnant females three times increased therapeutic dose of 6.0 mg/kg (60 mg/kg of the drug), the first group 1 on day 6 of pregnancy, the second from 7 - 14, third 15 and 19, the fourth group served as control and received 1% starch gel. On the 20th pregnancy day, the rats were euthanized with carbon dioxide. After slaughter and opening of the abdominal cavity have been removed the uterus with the fruit. Counted the number of yellow bodies of pregnancy, places of implantation, resorption, live and dead embryos. To assess the embryotoxic effect of the fruits were viewed under binocular magnifying glass to detect external anomalies, weighed, measured the cranio-caudal size, weight and diameter of placenta. Was determined pre - and postimplantation loss and total embryonic mortality of embryos. After inspection, the embryos from each rat was divided into two equal groups: the first were fixed in solution of Bouin for 14 days to study the internal organs of fetuses, and anomalies in developing fetuses, which are indications of teratogenic effect is determined by the method of J. G. Wilson (1965) in modification of the Department of embryology held the Academy of medical Sciences of the USSR (the scheme of transects made through the fetus); the second was fixed in 96 alcohol for study of the bone system after its dyeing by the method of Dawson (A. B. Dawson, 1926). The parameters obtained were processed by variation statistics with the help of simple comparisons of average according to the bilateral student’s t-test. The difference was determined at 0.05 level of significance. The calculations were performed using the “Student-200”. The results and discussion. As shown by the results of studies Triclafascid showed no embryotoxic activity when exposed to 3-fold increased therapeutic dose of 6.0 mg/kg po DV. So, overall, pre-and postimplantation mortality of fetuses in the experimental and control groups did not differ significantly, as with the introduction of the drug for 1-6 days of pregnancy and 7 -14 and 15 - 19 days. Based on these data it can be concluded that the drug Triclafascid has no negative influence on embryonic development. Values pre - and postimplantation and total embryonic mortality of experimental animals in comparison with control values, we can say that the drug did not induce the death of embryos in different periods of embryogenesis. The mass and size of the fruit also did not differ from the control, which indicates the absence of embryotoxic effect. A careful visual inspection of fruits in all experimental groups was not detected for any external malformations compared with controls. By the execution of nine sagittal sections of internal abnormalities, malformations of the internal organs, disorders of the topography was found. A teratogenic effect characterized by different anomalies of the internal organs of fetuses (Wilson’s method) and external defects were also not observed. When studying the skeletal system: the sizes of the rudiments of the shoulder; brachial; ulnar; radial; femoral; large and small tibial bones from experimental and control embryos were similar in metrics (length, mm). The condition of the bone system was unchanged (P>0,05). Therefore, Triclafascid showed no teratogenic activity when exposed at critical periods of embryogenesis of rats.